2021
DOI: 10.2196/25703
|View full text |Cite
|
Sign up to set email alerts
|

Mobile App–Reported Use of Traditional Medicine for Maintenance of Health in India During the COVID-19 Pandemic: Cross-sectional Questionnaire Study

Abstract: Background India follows a pluralistic system for strategic and focused health care delivery in which traditional systems of medicine such as Ayurveda, yoga and naturopathy, Unani, Siddha, Sowa Rigpa, and homoeopathy (AYUSH) coexist with contemporary medicine, and this system functions under the Ministry of AYUSH (MoA). The MoA developed a mobile app, called AYUSH Sanjivani, to document the trends of the use of AYUSH-based traditional and holistic measures by the public across India. Analysis of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…The health-seeking pattern of the people suggests a large section of the population, particularly in India has been consuming various AYUSH preparations and botanical immunomodulators in the hope of better protection against COVID-19 infection. Registration of more than 1.3 crore healthseekers in the AYUSH Sanjivani App indicates this trend [5].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The health-seeking pattern of the people suggests a large section of the population, particularly in India has been consuming various AYUSH preparations and botanical immunomodulators in the hope of better protection against COVID-19 infection. Registration of more than 1.3 crore healthseekers in the AYUSH Sanjivani App indicates this trend [5].…”
Section: Introductionmentioning
confidence: 94%
“…Any known co-morbidity or acute illness with or without symptoms at the time of study vaccine administration; Participants with a history of COVID -19 any time in the past or currently positive for SARS-CoV-2 by a standard RT-PCR assay; History of known hypersensitivity to any vaccine or any component of the study intervention (Vaccine or Ashwagandha); Any confirmed or suspected condition with impaired/altered function of the immune system or conferring a possible risk of SARS-CoV-2 infection as suggested by investigations (e.g. increased levels of Ddimer) 5. Women who are breast-feeding and pregnant; Individuals who are using any intervention (AYUSH or otherwise) for prophylaxis or with a purpose to increase immunity or influence immune system in any way e.g.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Findings have asserted that during the COVID-19 pandemic a large proportion of the population practiced AYUSH measures across the country and have benefitted considerably. 55 WHO is working with some research institutions around the world to select traditional medicine products with potential use for the treatment of COVID-19 after being investigated for clinical efficacy and safety. The WHO has been working with countries to ensure the safest and most effective use of traditional medicines, and it will continue to give support in exploring the benefits of traditional medicines.…”
Section: The Rationale For Integration Of Complementary Medicinementioning
confidence: 99%
“…Several medicinal plants from Ayurveda and traditional Chinese medicines which are known to modulate immune response were considered as potential therapeutic candidates (8, 12, 13, 14). Ayurvedic and other traditional herbal medicines are being popularly used in India to prevent and treat COVID-19 since the beginning of the pandemic (15, 16, 17,18). Safety and tolerability of Ayurvedic herbal medicines could be an added advantage for use in the community (19).…”
Section: Introductionmentioning
confidence: 99%